Relasi Keharmonisan Keluarga Dengan Minat Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam - Hanifah Nuraeni Awaliah; Agus Samsul Bassar; Ayi Juanda (Prodi PAI IAILM Suryalaya, 2024)
The low interest in learning students in Islamic Religious Education subjects is caused by various factors, one of which is family, this has an impact on understanding and practice in everyday life. The purpose of this study was to determine the relationship between family harmony and students' interest in learning Islamic Religious Education subjects at SDN 2 Tanjungkerta. This study is descriptive with a quantitative approach, the population is 140 with a sampling technique using purposive sampling and a sample of 46 respondents consisting of classes V and VI. Data collection techniques and research instruments use questionnaires, documentation and interviews. The results of the study the correlation results showing the Relationship between Family Harmony and Students' Interest in Learning PAI Subjects at SDN 2 Tanjungkerta, the calculation results obtained rs of 0.46, confirmed on the Guilford scale at the interval of 0.41-0.60 with sufficient classification. Then from the results of the determination test of 21% the relationship between family harmony and students' interest in learning PAI subjects at SDN 2 Tanjungkerta while 79% was influenced by other factors. The results of the hypothesis test show that the t_count is 3.4316 while the t_table based on the significance level α = 0.05 obtained a list of t_tables (0.95) (44) = 1.6802 the results can be concluded that t_count 3.4316 ≥ t_table 1.6802 so that Ha is accepted and Ho is rejected.